Hereditary spherocytosis with immunoglobulin A nephropathy - (:unkn) unknown (My University, 2010)
Hereditary spherocytosis is a familial hemolytic anemia. Immunoglobulin A (IgA) nephropathy associated with hereditary spherocytosis has not been reported in children. Here, we report a case of a 17-year-old boy with IgA nephropathy and hereditary spherocytosis. The patient was diagnosed with hereditary spherocytosis at the age of 12 years and splenectomy was done at the age of 15 years. Later, the patient presented with macroscopic hematuria and proteinuria. Kidney biopsy of the boy was consistent with IgA nephropathy. Treatment with angiotensin-converting enzyme inhibitor was started. The patient became free of proteinuria after the 6th month of therapy.
Keywords: Humans; Adolescent; Male; Biopsy; Kidney; Proteinuria; Hematuria; Glomerulonephritis, IGA; Spherocytosis, Hereditary